Optimism and Pessimism in Thomas Writings of Hardy`S: Exploring the Influence of Pessimism in Thomas Hardy's Writings (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Analyzing the factors that shaped an author's thoughts and work is a fascinating and difficultendeavor. The same holds true for Thomas Hardy. One of his books is a particularly fascinating exampleof what may be considered a substantial element of idea. This study explains how Hardy's pessimisminfluenced his writing. This darkness, albeit permeating his works, cannot be attributed to him as anindividual quality. The study also deduces the genuine foundation which inspires its appearance in all ofhis works. The tragic potential of his pessimistic worldview is further explored via the lens of hisphilosophy. - In general, Thomas Hardy is held in high regard as a worrier novelist whose works are fullof tear-jerking tragedies. The antagonistic situations in all of his books stem from the uncertain states ofthe part of the opportunity that arise depending on the characters' psycho-logical states and erraticmotivations, monetary varieties and hindrances, abnormalities of economic wellbeing and standards,communal, social, and ethnic misconception, a lack of trust in the conjugal relationship, the drive anddesire for sexual pleasure, the recorded mentalities and foundations, the height of illustrious families,and an abundance of recorded mentalities and foundations.